Incidence of Oral Cancer in a Tertiary Cancer Centre of Nepal: A Retrospective Study - Jaiswal, Pravin Kumar; Thakur , Prabhat; Thapa, Kapil (Europasian Journal of Medical Sciences, 2025)
Background: Oral cancer, which includes cancer of lips, gingiva, tongue, oropharynx, sinuses, and salivary glands, ranks fifth in its kind in Nepal. The incidence of oral cancer may differ among gender, age, and site. This study aims to address the questions regarding the incidence and trend of oral cancer occurrence. Methods: Oral cancer cases registered in the Head and Neck Oncology Department of Nepal Cancer Hospital & Research Centre, Lalitpur, Nepal from 01 Jan 2018 to 31 Dec 2019 were included in this study. The data were categorized under gender, site of a tumor, year of diagnosis, and age of patients at diagnosis and entered in RStudio version-1.3.1093 for analysis. Results: A total of 165 cases were found to be recorded where 74.5% were male and 24.5% were female. The most common site was the tongue (27.27%) followed by the mandibular alveolus (19.39%). The overall mean age was 53.71 years (95% CI: 55.73-51.68). The number of new cases was found to be increased by 35.71% from 2018 to 2019. Conclusion: A significant increase in the number of new cases indicates that there are deficiencies in handling oral cancer in Nepal. Reducing the production, import, and consumption of tobacco and related products as well as ensuring accessible health facilities for all may help control this disease.